2013
DOI: 10.1038/eye.2013.224
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcomes of corneal collagen crosslinking treatment

Abstract: Purpose To assess the effects of preoperative patient characteristics on clinical outcomes of corneal crosslinking (CXL) treatment in patients with progressive keratoconus. Methods This retrospective study comprised 96 eyes of 96 patients who had unilateral CXL treatment for progressive keratoconus. All patients underwent a complete ophthalmological examination and corneal topography at baseline and 1 year. Subgroup analyses were performed according to the age (o30 andZ30 years), gender, preoperative corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
39
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 23 publications
9
39
4
1
Order By: Relevance
“…Although we agree that age influences the outcome of the treatment, 2 our results, stratified into four subgroups (o18 years, 18-28 years, 29-39 years, and over 40 years), demonstrated a better functional and morphological outcomes in the population between 18 and 39 years of age.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…Although we agree that age influences the outcome of the treatment, 2 our results, stratified into four subgroups (o18 years, 18-28 years, 29-39 years, and over 40 years), demonstrated a better functional and morphological outcomes in the population between 18 and 39 years of age.…”
mentioning
confidence: 63%
“…We found that patients with a worse preoperative corrected distance visual acuity (CDVA, r20/40 Snellen equivalent) tend to experience more visual improvement after CXL treatment (Po0.001). 2 However, an older age (Z30 years) and a thinner cornea (thinnest pachymetry o450 mm) appear to be positive preoperative predictors for more flattening in maximum keratometry (P ¼ 0.024 and P ¼ 0.005, respectively). 2 Similarly, Vinciguerra et al 3 reported that age between 18 and 39 years has positive effect on the outcomes of CXL, and they found a significant association between the thinnest pachymetry and sphere change after CXL treatment.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 3 more Smart Citations